THE EFFECTIVENESS OF TENS IN REDUCING THE PAIN LEVELS AMONGST WOMEN IN THE FIRST STAGE OF GIVE BIRTH - Neni Nuraeni; Ade Kurniawati; Gugun Gundara (Ikatan Perawat Maternitas Indonesia Provinsi Jawa Barat, 2018)
The TENS instrument is a tool as an alternative of the non-pharmacological therapies to help give birth women in dealing with pain. There are electrodes in this tool that are useful for channeling electric wave to women’s back, that it stimulates the nerves in the area pain. The signal from TENS serves to disrupt the pain signals that affect the nerves and break the pain signal, as a result reducing patients’ pain levels. The aim of the study was to find out the effectiveness of TENS towards decreasing pain levels in the first stage of labour. The study applied the quasi-experimental research method with the one group pre-test design approach. The population was women the first stage of labour, and samples were selected using the accidental sample technique, and five women participated in this study. Data were analysed using the dependent T test. The results of the study obtained TENS with a frequency of 108 Hz and a voltage of 82 Volt is safe to patients’ skin. There was not a significant effect of TENS to the level of pain with ρ-value 0.374. It can be concluded that the TENS instrument that designed in this study is ineffective in managing labor pain especially the first stage. There is a need further research to test this instrument in the laboratory, and redesign it related to the instrument size and packaging.Keywords: give birth, pain, TENS